Continuous discharge monitoring of the Mirim-São Gonçalo system by the index velocity rating curve method - George Marino Soares Gonçalves; Guilherme Kruger Bartels; Luciana Shigihara Lima; Lukas dos Santos Boeira; Gilberto Loguercio Collares (Journal of Hydroinformatics, 2023)
The São Gonçalo Channel, located in the south of Brazil, is responsible for connecting the Mirim Lagoon to the Patos Lagoon, constituting the largest coastal lagoon system in Latin America. The assessment of its hydraulic variables is necessary given the importance of this channel for the region. Thus, this study aimed to evaluate the performance of the index velocity rating curve (IVRC) method, from velocity measurements provided by horizontal static-type acoustic Doppler profilers (H-ADCPs). For the two sections analyzed in this study (GS1 and GS2), IVRC models were developed considering the integrated velocity cell (IVC) method; the multi-cell velocity (MCV) method; the joint use of IVC and MCV; and a stage-mean velocity rating curve. The results point to an r2 of 0.986 (IVC), 0.998 (IVC + MCV), 0.534 (stage-mean velocity) at GS1, and r2 of 0.986 (IVC), 0.995 (IVC + MCV), and 0.815 (stage-mean velocity) at GS2. In both GS1 and GS2, results showed significant gains – for different flow conditions – on continuous estimations of flow velocities and discharges when considering the MCV + IVC method. The IVRC model that presented the best fit allowed the development of a time-series of discharges in the studied sites with high reliability. HIGHLIGHTS Assessment of the IVRC approaches on discharge estimations in a bi-directional natural channel.; Increment of reliability while moving from an SQRC on discharge estimations to an IVRC approach.; The possibility of registering complex flow situations from an in situ horizontal static-type ADPC.;